2017
DOI: 10.1002/2017gl073337
|View full text |Cite
|
Sign up to set email alerts
|

New insights into saline water evaporation from porous media: Complex interaction between evaporation rates, precipitation, and surface temperature

Abstract: Understanding salt transport and deposition patterns during evaporation from porous media is important in many engineering and hydrological processes such as soil salinization, ecosystem functioning, and land‐atmosphere interaction. As evaporation proceeds, salt concentration increases until it exceeds solubility limits, locally, and crystals precipitate. The interplay between transport processes, crystallization, and evaporation influences where crystallization occurs. During early stages, the precipitated sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 29 publications
10
53
0
1
Order By: Relevance
“…This was demonstrated experimentally, as the transition to third stage evaporation appeared earlier with lower cumulative evaporation for the sand with the lower number of nucleations (Figure 2), in agreement with other studies (Eloukabi et al, 2013;Gupta et al, 2014;Nachshon & Weisbrod, 2015;Shokri-Kuehni, Vetter, et al, 2017) that have shown that as long as the salt crust effectively delivers water by capillarity toward the salt atmosphere interface, its impact on evaporation is minor. These pillars probably were nucleation centers at the beginning of the evaporation process, and they have two important features: (1) to support the ESC structure and (2) to deliver solutes from the matrix to the growing ESC.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This was demonstrated experimentally, as the transition to third stage evaporation appeared earlier with lower cumulative evaporation for the sand with the lower number of nucleations (Figure 2), in agreement with other studies (Eloukabi et al, 2013;Gupta et al, 2014;Nachshon & Weisbrod, 2015;Shokri-Kuehni, Vetter, et al, 2017) that have shown that as long as the salt crust effectively delivers water by capillarity toward the salt atmosphere interface, its impact on evaporation is minor. These pillars probably were nucleation centers at the beginning of the evaporation process, and they have two important features: (1) to support the ESC structure and (2) to deliver solutes from the matrix to the growing ESC.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, several works visualized the precipitated salt crust with high-resolution X-ray scanners and scanning electron microscopy and showed that the typical pores of the salt crust are much smaller than those of the underlying soil (Norouzi Rad et al, 2013;Norouzi & Shokri, 2014); therefore, capillary flow of water from the wet matrix to the salt crust should take place ( Figure 1a2). This is in accord with other works that reported on capillary flow of water through ESC (Sghaier & Prat, 2009;Gupta et al, 2014;Shokri-Kuehni, Vetter, et al, 2017).…”
Section: 1029/2018gl078363supporting
confidence: 93%
See 1 more Smart Citation
“…Previous experiments related to the salt effects on the soil conditions and their hydrologic characteristics are summarized in Table . In these studies, the complex interactions between evaporation processes, soil salt distribution and the infiltration characteristics were mentioned and discussed (Shokri, ; Norouzi Rad & Shokri, ; Rad, Shokri, Keshmiri, & Withers, ; Dai, Shin, & Santamarina, ; Shokri Kuehni, Vetter, Webb, & Shokri, ).…”
Section: Introductionmentioning
confidence: 99%
“…Different phenomena affect the dynamics of the precipitated salt in a porous medium [31][32][33] . The effect of brine mobility and the initial liquid saturation has been studied 34-37 , showing that the drying fronts move with minute salt deposition for low brine concentration and low mobility.…”
Section: Introductionmentioning
confidence: 99%